Optimization of Extraction of Anthocyanins from Roselle (Hibiscus sabdariffa var. sabdariffa) in Aqueous Medium - Gartaula, Chanendra; Karki, Dhan Bahadur (Journal of Food Science and Technology Nepal, 2013)
The dried roselle (Hibiscus sabdariffa var. sabdariffa) calyces were studied for the extraction of anthocyanin in aqueous solution. The total anthocyanin content in dried roselle powder was found to be 310.48mg/100g of dry matter. The extraction temperature at 70°C gave the highest yield (66.69-70.61%), while at 90°C the degradation of anthocyanins occurred. The solid-liquid ratio revealed no significant effect (p>0.05), whereas the particle size showed a significant effect (p<0.05) on the extraction of anthocyanin. The yields of anthocyanin extraction for 300 and 600 μm particle powders were significantly higher (p<0.5) than that of 1180μm powder. Reduction in the particle size inversely increased the yield of anthocyanins. In conclusion, the extraction of anthocyanin from dried roselle calyces with an average particle size of 600μm using a solid-liquid ratio of 1:50 in aqueous medium with pH 7.0 at 70°C for 20min showed the maximum yield (69.84%). J. Food Sci. Technol. Nepal, Vol. 6 (66-72), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8263